1977
DOI: 10.1097/00006842-197701000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Crowding of Mice on Humoral Antibody Formation and Protection to Lethal Antigenic Challenge

Abstract: The effects of grouping (crowding) on humoral antibody response to typhoid paratyphoid vaccine and subsequent protection from a minimal lethal challenge dose of Salmonella typhimurium were studied in white Swiss-Webster mice. The data show a trend between the degree of crowding and antibody response. Geometric mean titers of high density grouped mice were significantly lower than the geometric mean titers of the less crowded mice. Also, there were significantly less antibody responders in the high density grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

1981
1981
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 12 publications
(12 reference statements)
0
35
0
1
Order By: Relevance
“…As early as 1890, Charrin [66] noted that forced physical exercise (a physical stressor) was associated with an increase in the mortality of rats infected with Bacillus anthracis. The same stressor appears to increase mortality in rabbits infected with Streptococcus pyogenes [67] and in rats infected with Mycobacterium tuberculosis [70], With mice, exposure to physical (cold) [68,69] or psycho logical (crowding) stressors [72] increases the mortality of animals infected with Salmonella typhimurium. In ponies too, resistance to this bacterium appears to be influenced by stressors of a prevalently physical type.…”
Section: Bacterial Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As early as 1890, Charrin [66] noted that forced physical exercise (a physical stressor) was associated with an increase in the mortality of rats infected with Bacillus anthracis. The same stressor appears to increase mortality in rabbits infected with Streptococcus pyogenes [67] and in rats infected with Mycobacterium tuberculosis [70], With mice, exposure to physical (cold) [68,69] or psycho logical (crowding) stressors [72] increases the mortality of animals infected with Salmonella typhimurium. In ponies too, resistance to this bacterium appears to be influenced by stressors of a prevalently physical type.…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…Edwards and Dean [72] studied the effects of psycho logical stress on humoral immune response to an extracel lular bacterium. Their experiment showed that, in mice infected with Sal.…”
Section: Stress a N D Infectious D Iseasesmentioning
confidence: 99%
“…For example, Les (1972)recorded tail lesions in C3H/HeJ mice, and noted that these were related to population density, though this is difficult to quantify from the data given in his paper. Edwards and Dean (1977) showed a reduction in antibody formation with extreme crowding (down to 8 cm 2 /mouse) with a density-dependent increased sensitivity to challenge with Salmonella typhimurium in unimmunized, but not immunized mice. Stocking density may also affect physiological variables.…”
Section: Introductionmentioning
confidence: 97%
“…Calhoun has noted the dissolution of maternal ties, homosexuality, and social withdrawal in rats when the population is allowed to increase in confined space (2)(3)(4). Secretions of the adrenal medulla and adrenal cortex have been related to crowding in animals (5), and crowding may also have a negative effect on humoral antibody formation (6).…”
mentioning
confidence: 99%